2011
DOI: 10.1063/1.3554253
|View full text |Cite
|
Sign up to set email alerts
|

Structure, magnetic, and dielectric properties of (1-x)BiFeO3-xBaTiO3 ceramics

Abstract: Structure, magnetization, and dielectric permittivity of (1-x)BiFeO3-xBaTiO3 (BFO-BT) ceramics have been studied as a function of BT content (x = 0.0, 0.1, 0.2, and 0.3). In situ synchrotron x-ray diffraction result of BFO reveals a rhombohedral (R)–orthorhombic (O)–cubic (C) phase transition near 820 and 850 °C upon heating. BFO-10%BT and BFO-20%BT exhibit a R–C transition near 760 and 740 °C, respectively. A C(R)–C transition takes place near 680 °C in BFO-30%BT. C(R) represents that a minor R phase coexists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Therefore, the lead-free ceramics were used in various applications, such as ultrasonic transducers [6][7][8][9], pyroelectric sensors [10] and actuators [11,12]. BFO-BTO system is proposed to be an important family of high-performance lead-free piezoelectric ceramics because of its good ferroelectric properties [13][14][15][16][17]. Additionally, Mn doping is a common method to enhance the piezoelectric properties and reduce the dielectric loss of the piezoelectric materials [15,16], thus, Mn modified BFO-BTO ceramic with good ferroelectric properties was chosen for transducer applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lead-free ceramics were used in various applications, such as ultrasonic transducers [6][7][8][9], pyroelectric sensors [10] and actuators [11,12]. BFO-BTO system is proposed to be an important family of high-performance lead-free piezoelectric ceramics because of its good ferroelectric properties [13][14][15][16][17]. Additionally, Mn doping is a common method to enhance the piezoelectric properties and reduce the dielectric loss of the piezoelectric materials [15,16], thus, Mn modified BFO-BTO ceramic with good ferroelectric properties was chosen for transducer applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two impurity peaks indicated by the symbols * and Δ are also observed because of slow phase formation kinetics of BFO. The impurity peaks might be formation of Bi 2 Fe 4 O 9 and Bi 24 Fe 2 O 39 and existence of such impurity peaks have been reported earlier by several authors[14,15]. The XRD patterns of BFO exhibit perovskite structure with rhombohedral unit cell and the lattice parameters are found to be a = b = 5.58 Å and c = 13.65 Å.…”
mentioning
confidence: 59%
“…The electrical properties are improved with the increase of BT content, generally by increasing the dielectric response and reducing the dielectric losses [18]. In fact, Wang et al [18] observed an increase of the dielectric constant in the x = 0-0.3 samples, from 30 (x = 0) to 500 (x = 0.3), at 1 MHz and room temperature.…”
Section: (1x)bifeo 3 -Xbatio 3 Systemmentioning
confidence: 97%